Case study on scheduling cyclic conveyor belts. (July 2021) - Bock, Felix; Bruhn, Henning
Highlights: Optimisation of cyclic production lines. Applied scheduling. Randomised algorithms. Abstract: We optimise the production line of a manufacturing company in southern Germany in order to improve throughput. While the optimisation problem is NP-hard in general, analysing production data we find that in practice the problem can be solved very efficiently by aggressive generation of random machine schedules.